Analysis of The Contention of Religious Ideology and Halal Industry in Social Media about Halal Logo Rebranding - Saidi, Saidi; Sazali, Hasan (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2024)
The Halal Product Guarantee Agency (BPJPH) halal logo design has pros and cons for Indonesian Muslims in terms of Arabic calligraphy, the shape of the halal logo, which resembles a wayang, and a total change from the previous halal logo of the Indonesian Council of Ulama (Majelis Ulama Indonesia). This research aims to analyze the phenomenon of the halal industry in Indonesia in the context of the contention between religious and industrial ideologies on social media, focusing the study on the controversial rebranding of the halal logo. This research uses a qualitative analysis method with a mass communication and political science approach to understand the substance and objectives of the various parties involved in the halal logo controversy on social media. This research indicates that a total change of the halal logo is not urgent in improving the quality of halal product guarantee services in Indonesia. The BPJPH halal logo design prioritizes artistic expression rather than Halal writing in Arabic as a sign that the product is "Halal," so it is difficult to read as a "Halal" sign. The essence of the halal logo is that it is a sign that the product has been certified halal by BPJPH so that the certainty of halal writing is easier and quicker for consumers to understand.